Edukasi Dan Pendampingan Ibu Nifas Dalam Pemberian ASI Eksklusif Di RSUD Padjonga Daeng Ngalle Takalar - Sumarmi Sumarmi; Ernawati Ernawati; Mantasia Mantasia; Sri Kurnia Sah Puteri (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Low rates of exclusive breastfeeding pose a threat to children's growth and development, affecting the quality of human resources. The majority of breastfeeding mothers discontinue breastfeeding within a few weeks postpartum due to perceived insufficient breast milk and dissatisfaction of the infant during breastfeeding. The objective of this community service activity is to enhance the knowledge, attitudes, and behaviors of postpartum mothers regarding breastfeeding their infants. The methods employed included lectures and question-and-answer sessions with mothers. This activity took place in the Postnatal Care Room of Padjonga Daeng Ngalle Hospital, Takalar Regency, on March 20, 2024, with the participation of six postpartum mothers. The results of education and support provided to postpartum mothers on exclusive breastfeeding using leaflets and flip charts showed that prior to the intervention, only 2 mothers (33.33%) had good knowledge, and after the education and support, this number increased to 5 mothers (83.33%) in the post-intervention test. Therefore, through education and support, motivation and behavioral changes in exclusive breastfeeding practices among postpartum mothers can be enhanced